From modelling to the model. A conversation with Laia Grau Balagueró - Martínez-Díez, Pablo; Santamaría-Varas, Mar; García-Pérez, Sergio (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
To close this thematic exploration of the use of data and methodologies that help us to describe, discover, predict, or simulate our urban environment, we interviewed Laia Grau Balagueró. Her vision, as urban planning manager of the city of Barcelona and with a broad experience linked to public administration and freelance professional activity as an architect, allows us to recognise the challenges and opportunities that the discipline of urban planning has regarding the transfer of this knowledge to the public policies that will define the urban model of our cities.
Keywords: Urban planning; Public policy; Knowledge transfer; Urban data